中文教師的教學信念如何影響教學實務How Teaching Beliefs of Chinese Language Teachers Influence Their Teaching Practice - 譚彩鳳Choi-Fung Tam (Higher Education Foundation, 2006)
本研究之目的是探討香港中文教師的教學信念及其與教學實務的相關性。研究對象是六位中學教師，教學年資由四年至三十一年不等。他們來自招收學生素質不同的學校，分為高、中、低三類。資料蒐集採用半結構式訪談及觀課進行。研究揭示教師的信念系統可歸為兩大類型，而主要的分歧在於教學範疇、教學方法、教學活動及師生在課堂中的角色。持傳授觀的教師支持舊課程，接受詳細講解經典範文的教學方式；然而，持啟發觀的教師則與新課程的理念相符。本研究也揭示教師的信念與教學實務，以及對學生的期望很大程度上是一致的，從研究發現顯示，要成功地實施課程，取決於教師是否認同新課程之目的與價值。 This study aims to investigate the beliefs of Chinese language teachers in Hong Kong and how these beliefs are related to their teaching. Six secondary teachers with teaching experience of 4 to 31 years were studied. They came from schools with high, medium and low quality of student intake. Data were collected from semi-structured interviews and classroom observations. The study finds that there are two predominant belief systems held by teachers. The major differences lie on the beliefs about scopes of teaching, instructional approaches, teaching and learning activities, and roles of teachers and students in classroom. The transmission-oriented teachers support the old Chinese language curriculum that requires the teaching of classical and exemplar texts in great detail. However, the view of the heuristics-oriented teachers is in line with the new curriculum. The results also reveal high degrees of consistency between teachers' professed beliefs and their teaching practices as well as their expectation on students. The findings of this study suggest that successful curriculum implementation depends on whether teachers agree with the aims and values of the new curriculum.